Synthesis and characterization of plasticized carboxymethyl cellulose based solid biopolymer electrolyte / Fitriyah Munirah Abdullah - Abdullah, Fitriyah Munirah (Faculty of Applied Sciences, 2017)
In this study, solid biopolymer electrolyte (SBE) has been prepared using carboxymethyl cellulose (CMC) and ammonium chloride (AC) by solution casting method. The effect of plasticizers ; ethylene carbonate (BC) and propylene carbonate (PC) was investigated. The ionic conductivity of CMC-AC-EC and CMC-AC-PC achieved at 2.715 x 10-5 Scm-1 and 3.672 x 10-5 Scm-1, respectively. The Fourier Transform Infrared (FTIR) spectra showed the occurrence of complexation between the SBE and AC salt. X-Ray diffraction (XRD) indicated that amorphous nature is higher in CMC-AC-PC. Differential Scanning Calorimetry (DSC) showed higher Tg for CMC-AC-PC. It can be concluded that PC is the promising plasticizer to enhance the ionic conductivity and performance of SBE system.